Textual Cultures of Medieval Italy Essays from the 41st Conference on Editorial Problems - Robins, William (University of Toronto Press, 2017)
Medieval Italy presented a rich array of discrete textual cultures, many of them specific to particular regions, professions, or groups of writers and readers. The essays in this collection consider how distinct habits of writing took root among specific communities in Italy between the early Middle Ages and the eve of the Renaissance.In examining how ideological concerns helped give shape to strategies of writing and how forms of communication influenced cultural developments, these case studies assess a wide range of texts, including legal treatises, saintly biographies, rhetorical handbooks, and vernacular poetry. As a whole, the collection makes the case for combining abstract analyses such as textual theory and intellectual history with more technical specialties such as editing and codicology. Rather than approaching pre-modern Italian textuality as something uniform, Textual Cultures of Medieval Italy engages with its fascinating plurality
Description based on online resource; title from PDF title page (publisher's Web site, viewed 13. Sep 2017)
Keywords: 1000-1400; DISCOUNT-B.; Textgeschichte; Italien; Konferenzschrift